Fluctuations in natural killer cell activity in early syphilis. Issue 1 (February 1983) - Jensen, J R; Thestrup-Pedersen, K; From, E
Abstract : The natural killer cell activity was studied in 25 patients with primary, secondary, or latent syphilis before and after treatment. In primary syphilis natural killer cell activity was increased, especially in patients lacking circulating lipoidal antibodies. In patients who had become seroreactive in the lipoidal tests it was depressed in those with secondary and latent syphilis. The natural killer cell activity thus becomes activated by the syphilitic infection but is significantly reduced during progression of the disease. The importance of the natural killer cell activity in controlling syphilitic infection is questionable.